EFEKTIVITAS PELAKSANAAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN PADA MASYARAKAT BADUY - Kosim Afendy (Prodi Hukum S1 - Fakultas Hukum - Universitas Pamulang, 2018)
Abstract This study intends to see the effectiviness of the marriage law Number 1 of 1974 concerning Marriege in its practical order for the Baduy Community and the obstacles experienced in implementing the law. The research method used is judicial emperical research based on data obtained from the field. The data collected was analyzed qualitatively nomatively. The result of the study show first, the implementation of Law Number 1 of 1974 concerning marriege has not been effectively implemented by the Baduy community. The obstacles to the implementation of the law were the lack of understanding of the baduy community in education and knowledge and still adhering to the customs and culture in the implementation of marriege.